The effects of heat input and electrode type on the mechanical properties of welded A309 stainless steel using a shielded metal arc welding - Anyanwu, Kingsley Onyekachi; Nzei, Harrison Ogochukwu; Onuoha, Chukwudike; Ehirim, Victor Ikechukwu (Universitas Muhammadiyah Surakarta, 2023)
This study deals with an experimental study to evaluate the influence of heat and electrode type on the mechanical properties of welded A309 stainless steel using shielded metal arc welding (SMAW). Samples were prepared with a welding angle of 45 deg. Seventy-eight samples made of A309 stainless steel were used in the experiments, in which half of the pieces were welded using A309 electrodes and half with E7018 electrodes. The samples were subjected to a tensile test and Charpy test accordingly. Several parameters, such as welding current (I), heat input (H), the final length of the tensile specimen (Lf), elongation percentage (%E), yield strength (σy), and impact energy, were observed. The results show that the increase in current from 100 to 225 A causes the growth of heat input from 0.56 to 1.26 kJ/mm, impacting the decrease of the percentage elongation and yield strength, including the energy impact reduction. On the other hand, all mechanical properties tested have relatively low heat input at 0.56 kJ/mm and relatively high heat input at 0.7 kJ/mm.